Geomorphosite Assessment at North Karangsambung -Karangbolong Geopark Kebumen, as Tools of Geotourism Development - Chusni Ansori; I. Wayan Warmada; Nugroho Imam Setiawan; Herry Yogaswara (UIR PRESS, 2021)
Geopark is a sustainable regional development concept that combines geological, biological, and cultural diversity through conservation and education activities to improve the community's welfare. Kebumen Regency has a National Geopark Karangsambung-Karangbolong (GNKK) covering 543,599 Km2 with 41 geosites, ten cultures, and eight biosite since 2018. The northern part of the area is a geological heritage that is widely used for field geological education. The study aims to identify and assess geosites and geomorphosite in the north area, describing the region's geomorphological processes and geological evolution. Field research was conducted to get an overview of geological diversity, geomorphology, and geosite and determine the selected geomorphosite. Geomorphosite assessment is done quantitatively using the Kubalikova method by assessing five main parameters that include; Intrinsic and scientific value, the value of education, economic value, conservation value, and added value. The scientific and intrinsic value of Pentulu Indah (PI) = 4, while Wagirsambeng = 3. Educational value of PI = 4, while Wagirsambeng = 2. Economic value is still not satisfactory, but P.I. = 2, while Wagirsambeng = 1.5. Conservation value of P.I. = 3.5, while Wagirsambeng = 2.5. Added value PI = 2.75 while Wagirsambeng = 1.5. Based on those, geomorphosite Pentulu Indah is 16,26 point or a good value (87.83 %) while Wagirsambeng is 10.5 point or fairly level (56.75 %).